Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0301006616675883
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Age on Visual–Vestibular Self-Motion Perception Using a Driving Paradigm

Abstract: Previous psychophysical research has examined how younger adults and non-human primates integrate visual and vestibular cues to perceive self-motion. However, there is much to be learned about how multisensory self-motion perception changes with age, and how these changes affect performance on everyday tasks involving self-motion. Evidence suggests that older adults display heightened multisensory integration compared with younger adults; however, few previous studies have examined this for visual-vestibular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 75 publications
0
16
0
1
Order By: Relevance
“… 147 Thus, it has been suggested that integration of visual and vestibular sensory information should be specially designed for use by older people. 148 The new generation of HDMs, such as the HTC VIVE, may eliminate some of the risks for sensory mismatch thanks to their tracking system, which allows the generated real-time 3D view to be updated according to the user’s orientation and movements. 149 Other simulator display technologies (such as spherical and angled 3-panel) that induce vection 150 (ie, illusions of self-motion) and, thus, a heightened degree of immersion, have been suggested as an alternative to HMDs.…”
Section: Challenges and Considerations For Using Vr In Clinical Or Camentioning
confidence: 99%
“… 147 Thus, it has been suggested that integration of visual and vestibular sensory information should be specially designed for use by older people. 148 The new generation of HDMs, such as the HTC VIVE, may eliminate some of the risks for sensory mismatch thanks to their tracking system, which allows the generated real-time 3D view to be updated according to the user’s orientation and movements. 149 Other simulator display technologies (such as spherical and angled 3-panel) that induce vection 150 (ie, illusions of self-motion) and, thus, a heightened degree of immersion, have been suggested as an alternative to HMDs.…”
Section: Challenges and Considerations For Using Vr In Clinical Or Camentioning
confidence: 99%
“…Current research efforts to counteract and/or postpone the negative effects of normal aging have been primarily focusing on physical and cognitive training protocols to prevent falls and enhance cognitive processes, thus partly ignoring the benefits associated with multisensory processing in healthy aging. Yet, the research reviewed in the previous section suggests that the aging brain tends to rely increasingly on multisensory integration by using information from several modalities so as to enhance cognition and perception, as well as to improve gait . The few attempts made to use multisensory principles as a solution to the age‐related alterations in sensory, cognitive, temporal, and motor processing have not truly exploited the variety of different types of sensory information available so as to optimize performance (e.g., walking tasks with eyes open or closed at different ground compositions) .…”
Section: Exploiting the Benefits Of Multisensory Processing For Succementioning
confidence: 99%
“…Older adults also have higher motion detection thresholds and they are less accurate in discriminating direction and speed (Atchley and Andersen, 1998;Bennett et al, 2007;Conlon et al, 2017;Norman et al, 2003;Pilz et al, 2010;Snowden and Kavanagh, 2006;Trick and Silverman, 1991). Thus, older adults might rely on vision less than younger adults (as seen in Ramkhalawansingh et al, 2017). This makes it not a priori obvious that older adults will respond more to visual information in all situations.…”
Section: Introductionmentioning
confidence: 99%